Home to Hickory Hollow : The Secret Keeper - Book 4 - Lewis, Beverly 1949- (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2013)
"Jennifer Burns has always had an 'old soul,' but joining the Amish world will challenge her spirit--and her heart--in ways she never expected"--Provided by publisher.
Keywords: Amish -- Fiction; Lancaster County (Pa.) -- Fiction; Domestic fiction; Christian fiction